Utilization of numerical techniques to predict the thermal behavior of wood column subjected to fire. Part A: Using finite element methods to develop mathematical model for wood column - Elshayeb M.; Rashid Ab Malik A.; Ideris F.; Hari Z.; Ab Razak N.; Siang J.E.L.; Anuar Z. (Trans Tech Publications Ltd, 2023)
The mathematical model to predict the temperature history for wood column is needed in order to determine its fire resistance when exposed to fire. In this paper, an intelligent methodology called Finite Element Method (FEM) of performing analysis for the square and circular wood columns by virtually or artificially developing a temperature history mathematical model. Numerical simulation model has been developed for the wood column by using two-dimensional mathematical model. The two-dimensional mathematical model was developed by using Galerkin's Weighted Residual technique. This model focuses on the regional material of the wood column for describing its thermal behavior. When the temperature history in a column and relevant materials properties are known, the strength of the column can be calculated at any time during fire. Therefore, the development of the temperature history mathematical model is a must before any further study to be carried out for the wood columns. The flow of convection will result in minimal increase in the rate of heat energy reaching the column core. The analysis shows that the temperature of the column increases with respect to the duration of exposure to fire.